A non-replicative antibiotic resistance-free DNA vaccine delivered by the intranasal route protects against canine leishmaniasis - Alonso, Ana; Alcolea, Pedro José; Larraga, Jaime; Peris, María Paz; Esteban, Adriana; Cortés, Alberto; Ruiz-García, Silvia; Castillo, Juan Antonio; Larraga, Vicente (Frontiers in Immunology, 2023)
Leishmania infantum is the etiological agent of zoonotic visceral leishmaniasis (ZVL). The disease is endemic in Central and South America, Central and South East Asia, and the Mediterranean basin. Dogs are the main reservoir, with an estimated prevalence of approximately 2.5 million dogs in Southern Europe. Current treatments cause side effects, disease recurrence, and drug resistance. Therefore, the development of vaccines against canine leishmaniasis is necessary. We have generated a DNA vaccine based on the non-replicative antibiotic resistance marker-free plasmid vector pPAL that contains the encoding gene for the L. infantum activated protein kinase C receptor analog (LACK). Homologous pPAL-LACK prime-boost intranasal administration confers efficacious protection in Beagle dogs with a reduction of clinical signs and a statistically significant reduction of the parasite burden in the bone marrow of more than 90% of dogs after experimental infection with highly infective promastigotes. This DNA vaccine elicits a robust cellular immune response skewed towards the Th1 profile.